2021
DOI: 10.1038/s41598-021-82834-9
|View full text |Cite
|
Sign up to set email alerts
|

LINC00665 promotes the progression of acute myeloid leukemia by regulating the miR-4458/DOCK1 pathway

Abstract: This study aimed to explore the role of LINC00665, miR-4458 and DOCK1 and their interactions in the development of acute myeloid leukemia (AML). The relative expression of LINC00665, miR-4458 and DOCK1 in AML samples was measured using qRT-PCR, and the protein level of DOCK1 in AML cell lines was examined using western blot. CCK8, BrdU, transwell, cell adhesion, and caspase-3 activity assays were carried out to evaluate the viability, proliferation, migration, adhesion, and apoptosis of AML cells, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Not surprisingly, DOCK family members have been engaged in a variety of pathologies, including carcinogenesis and impairments in the central nervous and immune systems [ 13 ]. Recent literatures showed that DOCK1 overexpression may participate in tumor development and metastasis, including breast cancer [ 14 ], bladder cancer [ 15 ], and acute myeloid leukemia [ 16 ]. More specifically, DOCK1 could promote the IL8-induced chemotaxis and mesenchymal transition of glioma cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, DOCK family members have been engaged in a variety of pathologies, including carcinogenesis and impairments in the central nervous and immune systems [ 13 ]. Recent literatures showed that DOCK1 overexpression may participate in tumor development and metastasis, including breast cancer [ 14 ], bladder cancer [ 15 ], and acute myeloid leukemia [ 16 ]. More specifically, DOCK1 could promote the IL8-induced chemotaxis and mesenchymal transition of glioma cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, only 4 arlncRNAs (LINC00665, [ 34 , 35 ] PCED1B-AS1, [ 36 , 37 ] LINC00324, [ 38 ] and ZEB1-AS1 [ 39 ] ) have been biologically validated in other tumors. However, as far as we know, these 9 arlncRNAs have not been fully validated in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis showed that the expression of LINC00665 was negatively correlated with miR-4458 in AML bone marrow tissue, and the results of qRT-PCR also displayed that miR-4458 was downregulated in AML tissue ( Yang et al, 2021b ). The luciferase reporter assay further proved that LINC00665 and miR-4458 could directly interact in AML cells ( Yang et al, 2021b ). Moreover, they demonstrated that LINC00665 promoted the proliferation, adhesion, and migration of AML cells but restricted the apoptosis of AML cells by sponging miR-4458 ( Yang et al, 2021b ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
“… Yang et al (2021b) revealed that LINC00665 was significantly upregulated in AML tissues and cell lines. Correlation analysis showed that the expression of LINC00665 was negatively correlated with miR-4458 in AML bone marrow tissue, and the results of qRT-PCR also displayed that miR-4458 was downregulated in AML tissue ( Yang et al, 2021b ). The luciferase reporter assay further proved that LINC00665 and miR-4458 could directly interact in AML cells ( Yang et al, 2021b ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%